(untitled) (Journal of Oriental Studies, 2016)
В этой статье описывается переселение в Казахстан первых китайских мигрантов, становление китайской диаспоры в Казахстане, их социальное положение и место в нынешнем Казахстанском обществе. The name of article is “Formation of Chinese Diaspora in Kazakhstan and it’s social position in society”. As the title implies, the article describes the main stages of Chinese migration to Kazakhstan, formation of Chinese Diaspora and their social position in nowadays Kazakhstan society.